2019
DOI: 10.1111/ans.15568
|View full text |Cite
|
Sign up to set email alerts
|

Systematic use of the serum C‐reactive protein concentration and computed tomography for the detection of intestinal anastomotic leaks

Abstract: Background This study aimed to characterize the time‐dependent relationship between serum C‐reactive protein (CRP) and anastomotic integrity in the early post‐operative period and to develop a systematic use of CRP and computed tomography. Methods Patients aged 18 years or over who had the formation of a left‐sided colonic or a colorectal anastomosis, in Royal Sussex County Hospital, were included. The post‐operative day (POD) CRP cut‐off values were calculated according to receiver operating characteristic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…CRP levels, in line with other studies, measured on the 4th day provided the highest diagnostic accuracy for identifying postoperative complications, whereas WBCC contributed little information [174]. These results were supported by other retrospective [176] and prospective studies [170]. A further study demonstrated that in patients who developed an AL, increased WBCC only occurred after 6 days following surgery [165].…”
Section: Leukocytes Neutrophils and Intestinal Damage Markerssupporting
confidence: 80%
See 1 more Smart Citation
“…CRP levels, in line with other studies, measured on the 4th day provided the highest diagnostic accuracy for identifying postoperative complications, whereas WBCC contributed little information [174]. These results were supported by other retrospective [176] and prospective studies [170]. A further study demonstrated that in patients who developed an AL, increased WBCC only occurred after 6 days following surgery [165].…”
Section: Leukocytes Neutrophils and Intestinal Damage Markerssupporting
confidence: 80%
“…In contrast to these results, recent research has shown that serum CRP levels can become elevated several days before clinical AL diagnosis and are significantly raised in comparison to patients who have an uneventful post-operative recovery [165][166][167][168][169][170][171][172][173][174][175][176][177]. Currently, the main issue with using serum CRP levels for AL prediction or diagnosis is the lack of definitive cut-off values.…”
Section: C-reactive Protein Albumin and Procalcitoninmentioning
confidence: 96%
“…Several studies have reported serum CRP as an early predictor of AL after colorectal surgery. 7 , 14 , 15 A recent prospective multicenter study involving 833 patients further demonstrated that a change in CRP level of more than 50 mg/L between any 2 consecutive days after surgery had a sensitivity of 85% in predicting AL. 16 However, the use of CRP in early AL diagnosis remains controversial, with two main limitations.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most widely studied biomarker for prediction of AL is CRP [13,14,[24][25][26][27][28][29][30][31][32][33][34][35][36][37]. NEUT and WBC counts are also candidate indicators; however, their value in prediction of AL is still controversial [38].…”
Section: Discussionmentioning
confidence: 99%